Transposition of the great arteries with total anomalous pulmonary venous connection in a 1½year-old child: Pulmonary arterial hypertension - An advantage - Rose Okwunu Abah; Atul Prabhu; Ashish Katewa; Balswaroop Sahu (Wolters Kluwer Medknow Publications, 2021)
Transposition of the great arteries with total anomalous pulmonary venous connection is a rare anomaly with varied management approach depending on the time of presentation; the management of cases which present early is usually by anatomical surgical approach while late presentation is by physiologic approach. This is due to early left ventricular mass regression as a result of the absence of volume and pressure load to the left ventricle (LV). We report a late presentation (at 1½ years of age) that had a successful anatomic surgical correction because the LV was "prepared" by both pressure and volume load from pulmonary arterial hypertension and large ostium secundum atrial septal defect.